A prototype for hands-free Filipino text messaging - Eala, Maria Christa Felize D. (2011)
Accidents caused by use of mobile phones while driving have increased over the years. For people with on-the-go lifestyles using mobile phones while on the road cannot be avoided. With the advancement in the Automatic Speech Recognition technology, hands-free texting is possible and has been implemented. However, these applications do not support the Filipino Language and may result in very low accuracies and errors in the recognition process. The Filipino speech recognizer, trained and developed using CMU SPHINX, achieved an average accuracy of almost 80%. To test its performance, the recognizer was then ported into the Apple iPhone using XCode and iPhone SDK. The application, which serves as a prototype for a hands-free text messaging application, produced an average response time of 1.036 seconds.